2010
DOI: 10.1185/03007995.2010.505545
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of flavocoxid compared to naproxen for management of mild to moderate OA

Abstract: In patients over 65 years of age who suffer from mild to moderate OA, flavocoxid may result in lower overall costs, despite a higher acquisition cost. Managed care organizations should consider total health care costs in the decision to include flavocoxid as a covered benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The most frequent methods were Delphi or modified Delphi process ( n = 10), 13,36,37,41,42,47,55,58,61,66 while 2 used the SHELF method 63,64 ; both methods rely on multiple rounds of discussion to build consensus among experts. Elicitations were frequently done virtually or over the phone ( n = 13) 14,36,41,46,48,50,53,55,57,66,67,70,71 while only 5 specified that the elicitation was conducted in person. 38,39,48,51,60 Web- or spreadsheet-based elicitation tools were used to facilitate data collection in 9 elicitations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent methods were Delphi or modified Delphi process ( n = 10), 13,36,37,41,42,47,55,58,61,66 while 2 used the SHELF method 63,64 ; both methods rely on multiple rounds of discussion to build consensus among experts. Elicitations were frequently done virtually or over the phone ( n = 13) 14,36,41,46,48,50,53,55,57,66,67,70,71 while only 5 specified that the elicitation was conducted in person. 38,39,48,51,60 Web- or spreadsheet-based elicitation tools were used to facilitate data collection in 9 elicitations.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently used form of mathematical aggregation was linear pooling ( n = 18). 12,39,40,42,46,49,51,52,55,57,59,61,62,64,65,67,68,71 Performance measures, 73,74 in which the experts’ estimates are weighted based on their responses to seed variables (also known as calibration questions) with answers known to the facilitator but unknown or not readily available to the experts, were only used in 2 studies. 48,57 No other weighting, such as by expert’s reported level of confidence, was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a phase-IV-like postmarketing study showed that flavocoxid was well-tolerated in previously NSAID (including celecoxib) intolerant patients who ceased or decreased gastroprotective use by over 30% [11]. Walton et al [68] performed a cost analysis which suggests that this safety advantage would make flavocoxid less expensive compared to generic naproxen in a medicare population over a one-year time frame. A well-controlled endoscopy study is needed to definitively judge flavocoxid's gastrointestinal safety.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical trials and phase-IV study cited above, in addition to national rheumatologist opinion, and literature comparisons were utilized to perform a pharmacoeconomic analysis. This analysis demonstrated that the cost of care, using a "one year window of treatment" decision model to estimate the total costs associated with use of flavocoxid or naproxen for patients with mild to moderate OA over age 65, that Limbrel (flavocoxid) was lower in the flavocoxid treated patients in the first year of therapy [130]. Thus, even though generic NSAIDs may have a cheaper initial cost, when the cost of gastroprotective medications and side effect treatment, including hospitalizations for upper GI events are taken into account, flavocoxid is the safer and less expensive option.…”
Section: Flavocoxid Clinical Safety and Efficacymentioning
confidence: 96%